Modeling of Irregularly Shaped Two – Dimensional Objects - Arthur J. Keyan (Изд-во НАН РА)
In this paper the description of the two - dimensional modeling program of irregularly shaped objects is given. The program is very easy to use, it works fast and has many other advantages.
Keywords: Mathematics; Computer software; Algorithm